Role Of Self-efficacy As A Mediator In The Relationship Between Parental Restriction And The Quality Of Cross-Ethnic Friendships - Andrea, Kelvin; Muttaqin, Darmawan (Psychological Research on Urban Society, 2024)
Urban environments can help form cross-ethnic friendships among individuals. However, many parents impose restrictions on their children’s ability to develop friendships, particularly between Chinese and Javanese ethnic groups. These parental restrictions directly impact the quality of friendships and are believed to be mediated by self-efficacy. This study examined the role of self- efficacy as a mediator in the relationship between parental restrictions and the quality of cross- ethnic friendships. The study involved 400 emerging adults aged 18–25 years, comprising 200 Chinese and 200 Javanese individuals. Parents’ peer restriction, Cross-Ethnic Friendship Self- Efficacy, and McGill Friendship Questionnaires-Friendship Function were used to measure parental restriction, self-efficacy, and friendship quality. Hypotheses were tested using the Sobel test. The study found that self-efficacy did not mediate between parental restriction and friendship quality. The findings suggest considering the role of friendship duration on interethnic friendship quality consistent with the principles of proximity and homophily.